THE EFFECT OF FINANCIAL LITERATURE AND BIG FIVE PERSONALITY TRAIT ON INVESTMENT INTENTION ON MILLENIALS IN PANDEMIC ERA - Andreas Wijaya; Tannia Tannia; Vallent Wonda; Ashifa Zulfa Faujian; Elisabeth Vebrin (Universitas Pelita Harapan, 2022)
The outbreak of the corona virus had made significant changes in VUCA era, where as volatility, uncertainty, complexity, and ambiguity hit harder economic, including financial sector. As the consequences of government policies to imposed lockdown, Stock market has declined drastically, on the other hand the number of investor increased compared to the previous years. This anomaly phenomenon shows there is another variable generates investment intention. Previous studies, the topic of financial management behavior studies still limited, especially on the psychological side of humans. This study revealed factors such as financial literacy and big personality traits from the point of view of men and women to reveal this phenomenon, using a questionnaire in data collection and a Likert scale, processing that carried out using the SMART PLS test tool. the result is that female respondents get a greater significance value than male respondents, it can be concluded that financial literacy is needed by women. For the moderating results in this study, it shows that men have a moderating influence while women do not have moderation. This study used 195 respondents, so that in the future it can increase the number of respondents to strengthen the research model. In addition, this research is still ongoing in the Jakarta area, so it can be a consideration for conducting further research such as adding respondents outside Jakarta.